2022
DOI: 10.1016/j.jisako.2021.12.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of vancomycin-soaking of the graft in anterior cruciate ligament reconstruction

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Sterility tests were carried out on samples of reconstituted products of intravenous antibiotic preparations (Ghert et al, 2022). In this study, the most widely used antibiotic is the third-generation cephalosporin group, so sterility testing was carried out at the Palembang Health Laboratory Center (BBLK), which showed that the results of ceftriaxone intravenous antibiotic preparation products reconstituted by one of the private hospitals in Palembang with limited facilities and aseptic techniques that are not optimal to produce preparations that are free of microorganisms (sterile) (Rodriguez-Merchan and Ribbans, 2022). This is because the work of ceftriaxone antibiotics is to inhibit and kill germs.…”
Section: Discussionmentioning
confidence: 99%
“…Sterility tests were carried out on samples of reconstituted products of intravenous antibiotic preparations (Ghert et al, 2022). In this study, the most widely used antibiotic is the third-generation cephalosporin group, so sterility testing was carried out at the Palembang Health Laboratory Center (BBLK), which showed that the results of ceftriaxone intravenous antibiotic preparation products reconstituted by one of the private hospitals in Palembang with limited facilities and aseptic techniques that are not optimal to produce preparations that are free of microorganisms (sterile) (Rodriguez-Merchan and Ribbans, 2022). This is because the work of ceftriaxone antibiotics is to inhibit and kill germs.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness is due to the low price of vancomycin and the simplicity of the procedure. Rodriguez-Merchan and Ribbans summarized the knowledge on the in vitro and in vivo studies performed on the vancomycin soaking procedure in their current concept review [ 39 ]. They concluded that, beside the published level III studies, prospective clinical trials are necessary to answer questions such as if this treatment should be used universally in all ACLRs, if incubation time might have an effect and if the vancomycin concentration might be adapted.…”
Section: Discussionmentioning
confidence: 99%
“…So zeigt die Kombination aus dem hydrophilen Gentamicinsulfat mit dem hydrophoberen Gentamicin-Crobefat Vorteile bez. der Freisetzungskinetik [44,45] Die Anwendung wird durch Editorials, Reviews und Metaanalysen gestützt, die eine deutliche Risikoreduktion hinsichtlich eines Auftretens von Infektionen zeigen [63,64,65,66]. Da keine weitreichenden RCTs zu diesem Thema existieren und die Erkenntnisse vor allem auf Beobachtungsstudien basieren, halten sich Zweifel bez.…”
Section: Weitere Trägermaterialienunclassified
“…with regards to the occurrence of infections [63,64,65,66]. Since there are no RCTs with comprehensive evidence on this topic and findings are mainly based on observational studies, doubts have been voiced about the possible long-term damage to the implant, the development of resistance, and the risk-benefit ratio (with infection rates in aseptic procedures <1% [64]), which limits their overall use [67].…”
Section: Topical Antibiotics As Prophylaxismentioning
confidence: 99%